2011
DOI: 10.1093/scan/nsr021
|View full text |Cite
|
Sign up to set email alerts
|

Neural contributions to flow experience during video game playing

Abstract: Video games are an exciting part of new media. Although game play has been intensively studied, the underlying neurobiology is still poorly understood. Flow theory is a well-established model developed to describe subjective game experience. In 13 healthy male subjects, we acquired fMRI data during free play of a video game and analyzed brain activity based on the game content. In accordance with flow theory, we extracted the following factors from the game content: (i) balance between ability and challenge; (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
138
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(154 citation statements)
references
References 53 publications
14
138
1
1
Order By: Relevance
“…In this case, we speculate that the VLPFC was involved in the cognitive control of memory, because activation was observed in both the boredom and the flow conditions. In contrast to a previous study [7], we observed no significant activation of premotor or supplementary motor areas. Activation of these areas is probably not essential for flow, but may be induced by task characteristics.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In this case, we speculate that the VLPFC was involved in the cognitive control of memory, because activation was observed in both the boredom and the flow conditions. In contrast to a previous study [7], we observed no significant activation of premotor or supplementary motor areas. Activation of these areas is probably not essential for flow, but may be induced by task characteristics.…”
Section: Discussioncontrasting
confidence: 99%
“…Klasen et al [7] used functional magnetic resonance imaging (fMRI) to evaluate brain activity during flow and demonstrated increased activity in midbrain reward structures as well as a complex network of sensorimotor, cognitive and 6 emotional brain circuits during a state of flow. However, the level of flow was not assessed, and it is not clear whether participants were able to enter a full state of flow when their heads were fixed in the magnetic resonance scanner.…”
Section: Introductionmentioning
confidence: 99%
“…The questionnaire was constructed based on a literature review regarding the different components of motivation according to the concept of flow (Csikszentmihalyi, 2000) in relation to video games (Klasen, Weber, Kircher, Mathiak, & Mathiak, 2012), and media enjoyment (Weber, Tamborini, Westcott-Baker, & Kantor, 2009). One version was used for the VR task and another for the traditional memory task.…”
Section: Presence Motivation and Cybersickness Questionnairesmentioning
confidence: 99%
“…Neural correlates for the flow experience were studied by Berta et al (2013) and Klasen et al (2012). Berta et al (2013) studied the use of electroencephalogram (EEG) for user status monitoring in games.…”
Section: Neural Correlatesmentioning
confidence: 99%